Design and characterization of a biomimetic composite inspired to human bone. (6th March 2014) - Libonati, F.; Colombo, C.; Vergani, L.; Pantelakis, Spiros; Berto, Filippo; Lazzarin, Paolo
ABSTRACT Many biological materials are generally considered composites, made of relatively weak constituents and with a hierarchical arrangement, resulting in outstanding mechanical properties, difficult to be reached in man‐made materials. An example is human bone, whose hierarchical structure strongly affects its mechanical performance, toughness in particular, by activating different toughening mechanisms occurring at different length scales. At microscale, the principal toughening mechanism occurring in bone is crack deflection. Here, we study the structure of bone and we focus on the role of the microstructure on its fracture behaviour, with the goal of mimicking it in a new composite. We select the main structural features, the osteons, which play a crucial role in leading to crack deflection, and we reproduce them in a synthetic composite. The paper describes the design, manufacturing and characterization of a newly designed composite, whose structure is inspired to the Haversian structure of cortical bone, and that of a classic laminate developed for comparative reasons. We conclude with a critical discussion on the results of the mechanical tests carried out on the new composite and on the comparative laminate, highlighting strengths and shortcomings of the new biomimetic material.